Social Policy Review 26 : Analysis and Debate in Social Policy, 2014 - Fenger, Menno; Irving, Zoe; Farnsworth, Kevin (Book collections on Project MUSE., 2014)
This important annual volume examines the economic and political challenges that have confronted governments over the past year, and highlights the diverse ways in which nations have responded, providing academics and students with an invaluable up-to-date analysis of the current state of social policy.